2018
DOI: 10.1128/iai.00117-18
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-18 Is Critical for Mucosa-Associated Invariant T Cell Gamma Interferon Responses to Francisella SpeciesIn Vitrobut NotIn Vivo

Abstract: Mucosa-associated invariant T (MAIT) cells are a subset of innate T cells that express a semi-invariant Vα chain paired with limited Vβ chains. MAIT cells are activated by riboflavin metabolite derivatives presented by the nonpolymorphic major histocompatibility complex class I (MHC-I)-like molecule MR1. The precise mechanisms required to activate MAIT cells are an area of intense interest. Here we used two closely related intracellular pathogens with distinct inflammasome activation phenotypes to probe the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 58 publications
2
20
0
Order By: Relevance
“…Furthermore, peripheral blood mononuclear cells or the THP1 monocytic cell line exposed to E. coli (riboflavin-synthesizing) or E. faecalis (non-riboflavin-synthesizing) produce IL-12 and IL-18 via a Toll-like receptor 8 (TLR8) pathway, and both cytokines are required for MAIT cell activation 59 . However, a recent study showed that although IL-18 is required for MAIT cell activation by F. tularensis in vitro, this cytokine is not essential for MAIT cell IFNγ production in in vivo infection 49 . Bacterial infection in vivo might induce MAIT cell activation through a more complex immune cell crosstalk, involving TLRs expressed by antigen-presenting cells (APCs) 48,59 .…”
Section: Mr1-independent Activation Of Mait Cells Tcr-mentioning
confidence: 98%
See 2 more Smart Citations
“…Furthermore, peripheral blood mononuclear cells or the THP1 monocytic cell line exposed to E. coli (riboflavin-synthesizing) or E. faecalis (non-riboflavin-synthesizing) produce IL-12 and IL-18 via a Toll-like receptor 8 (TLR8) pathway, and both cytokines are required for MAIT cell activation 59 . However, a recent study showed that although IL-18 is required for MAIT cell activation by F. tularensis in vitro, this cytokine is not essential for MAIT cell IFNγ production in in vivo infection 49 . Bacterial infection in vivo might induce MAIT cell activation through a more complex immune cell crosstalk, involving TLRs expressed by antigen-presenting cells (APCs) 48,59 .…”
Section: Mr1-independent Activation Of Mait Cells Tcr-mentioning
confidence: 98%
“…1). MAIT cells express high levels of IL-18 receptor (IL-18R) and IL-12R, and IL-18 and IL-12 have emerged as the major cytokines that activate MAIT cells upon bacterial or viral infection 43,45,[49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68] ( TaBle 2). During bacterial infection, blockade or deletion of the IL-12p40 subunit impairs MAIT cell control of intracellular growth of F. tularensis and M. bovis 43,45 .…”
Section: Mr1-independent Activation Of Mait Cells Tcr-mentioning
confidence: 99%
See 1 more Smart Citation
“…MAIT cells have been analyzed in several mouse models of bacterial infection, demonstrating their role in protecting against pathogenic organisms such as Francisella tularensis ( 33 , 70 ), Klebsiella pneumoniae ( 32 ), Mycobacterium bovis BCG ( 54 ), and Legionella longbeachae ( 34 ). Riboflavin-based antigens are likely produced not only by pathogenic microorganisms during infection, but also by commensal microorganisms.…”
Section: Mr1-antigen Recognition In Physiological Settingsmentioning
confidence: 99%
“…MAIT cells have been described as “innate-like” rapid responders, with a memory-like phenotype. However, like conventional T cells, MR1-antigen alone is insufficient to drive an optimal MAIT cell response, with co-stimuli including cytokines and/or surface co-receptors required ( 67 ) and able to enhance MAIT responses to antigen stimulation ( 96 99 ), although in vitro findings have not always translated to in vivo studies ( 70 ). Additionally, polarizing effects on MAIT cell function have been demonstrated.…”
Section: The Context Of Antigen Recognition Determines Mait Cell Respmentioning
confidence: 99%